Effect of Taijiquan Exercise on Rehabilitation of Male Amphetamine-Type Addicts - Zhang, Zhilei (Evid Based Complement Alternat Med, 2020)
Taijiquan is a traditional Chinese sport that is classified as a moderate exercise. Recent studies have evaluated the effectiveness of Taijiquan in substance abuse rehabilitation. Objective. To test the rehabilitation effect of Taijiquan exercise in patients with amphetamine (ATS) drug dependence. Methods. The effect of Taijiquan intervention was tested by parallel control experiment: Taijiquan group (n = 38) and control group (n = 38). The factors between the experimental groups were the group (Taijiquan group and the control group), and the factors within the group were the test time (before and after intervention). Repeated measurement analysis of variance was used to compare the two groups, and the factors that may affect the results were included in the covariance. Results. Taijiquan exercise promoted the balance control ability of ATS dependent patients (p = 0.014, η(2) = 0.064), increased the overall sense of health (p = 0.029, η(2) = 0.100), vitality (p = 0.030, η(2) = 0.056), and mental health (p = 0.016, η(2) = 0.061), improved trait anxiety (p = 0.028, η(2) = 0.053), and reduced drug craving (p = 0.048, η(2) = 0.048). Conclusion. Taijiquan exercise is beneficial to the physical and mental recovery of dependent patients, and the physical and mental benefits of exercise may have an effect on drug craving, which is of the most important significance for addicts to quit drugs and prevent relapse. The study is registered on the Chinese Clinical Trial Registry (No. ChiCTR1800015777).